2007
DOI: 10.1007/s11101-006-9013-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity and defensive properties of diterpenoid alkaloids

Abstract: Diterpenoid alkaloids are compounds of pharmacological interest. Forty four C 19 norditerpenoid (NDAs) and 23 C 20 diterpenoid (DAs) alkaloids isolated from Aconitum, Delphinium and Consolida species were tested for their insecticidal effects (antifeedant and toxic) on Spodoptera littoralis and Leptinotarsa decemlineata, their cytotoxicity on tumoral cell lines with several multidrug resistance mechanisms, and their antiparasitic effects against Trypanososma cruzi and Leishmania infantum. Overall, C 19 nordite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…litura respectively. The present work is consistent with the findings of Reina and Gonzalez‐Coloma, who observed that norditerpenoid and 23C 20 diterpenoid from Aconitum , Delphinium and Consolida species showed larvicidal activity against S. littoralis and Leptinotarsa decemlineata . Similarly, Senthil Nathan and Kalaivani reported that azadirachtin showed concentration‐dependent larval mortality against S. litura .…”
Section: Discussionsupporting
confidence: 93%
“…litura respectively. The present work is consistent with the findings of Reina and Gonzalez‐Coloma, who observed that norditerpenoid and 23C 20 diterpenoid from Aconitum , Delphinium and Consolida species showed larvicidal activity against S. littoralis and Leptinotarsa decemlineata . Similarly, Senthil Nathan and Kalaivani reported that azadirachtin showed concentration‐dependent larval mortality against S. litura .…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have demonstrated that diterpenoid alkaloids often had damage to tumor cells and normal cells with their cytotoxicity that interfere the DNA synthesis during the cell divisions. Several C19-norditerpenoids like neoline, aconitine, pubescenine, 14-deacetylajadine, lycoctonine, dehydrotakaosamine and ajadelphinine had irreversible effects on SkMel25, SW480, HeLa and PC12 cell lines 26 , 27 . As it’s known to all, cardiomyocyte damage is one of the most important factors for DDAs’s cardiotoxity.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence transients are shown in Fig. The above-mentioned lifetime results can be rationalized in terms of alternations in radiative and non-radiative decay pathways (eqn (2) and (3)) of SANG in the presence of confined micellar environments. Iminium and alkanolamine forms in water exhibit a single exponential decay (collected at 580 nm and 415 nm, respectively) with lifetimes of 2.37 ns and 3.16 ns, respectively.…”
Section: Time Resolved Studymentioning
confidence: 86%